PARENTS’ EXPERIENCES OF PARENTING AN ADOLESCENT ABUSING SUBSTANCES - Kalam, Aziza; Mthembu, Thuli Godfrey (Social Work/Maatskaplike Werk, 2018)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Adolescent substance abuse is one of the social and public health concerns that appears to influence parenting, but little is known about the parents’ experiences of parenting adolescents who are abusing substances. An exploratory, descriptive, qualitative approach was employed with in-depth interviews to explore the parents’ experiences of parenting adolescents abusing substances. Thematically analysed data produced three themes: parenting my way, perceived barriers and facilitating factors. Authoritarian, authoritative and permissive parenting styles were discussed to create a supportive environment to enhance parents’ coping strategies. This work contributes to existing knowledge on parents dealing with adolescent substance abuse by providing strategies to enhance parenting.